2015
DOI: 10.1039/c5ra16023e
|View full text |Cite
|
Sign up to set email alerts
|

Killing cancer cells by delivering a nanoreactor for inhibition of catalase and catalytically enhancing intracellular levels of ROS

Abstract: Intracellular hydrogen peroxide levels have the potential to be exploited in cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 76 publications
0
78
0
Order By: Relevance
“…The surface area and pore volume were sharply reduced to 29 m 2 /g and 0.22 cm 3 /g, respectively, which provided further supportive evidence of HTCC coating. Lee has reported that the BET surface area was dramatically reduced from 1198 m 2 /g to 20 m 2 /g after heavy aminotriazole loading of copper-impregnated MSNs [31]. Additionally, the loss of the hysteresis loop affirms that the pores were blocked by the polymer coating and lost their mesoporous structure characteristics.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The surface area and pore volume were sharply reduced to 29 m 2 /g and 0.22 cm 3 /g, respectively, which provided further supportive evidence of HTCC coating. Lee has reported that the BET surface area was dramatically reduced from 1198 m 2 /g to 20 m 2 /g after heavy aminotriazole loading of copper-impregnated MSNs [31]. Additionally, the loss of the hysteresis loop affirms that the pores were blocked by the polymer coating and lost their mesoporous structure characteristics.…”
Section: Resultsmentioning
confidence: 98%
“…The 1088 cm −1 broad absorption band was ascribed to Si–O–Si (siloxane) strething vibrations. Almost no C–H stretch peaks are present in the MSN samples, implying that the surfactant template of CTAB was completely extracted [31]. The peak at 1481 cm −1 for the HTCC spectra can be assigned to the C–H bending vibration of –N(CH 3 ) 3 + , confirming the existence of a quaternized amine group in the CS backbone [32].…”
Section: Resultsmentioning
confidence: 99%
“…The expressions of respective vascular protein markers were investigated using Western blot method. The proteins were extracted by following the reported procedure . The tissue block was cleaved, and the cells were collected and homogenized using the radioimmunoprecipitation assay (RIPA) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, when used in combination with copper, DSF becomes a strong inducer of radical oxygen species (ROS) [27][28][29][30]. Despite its powerful anticancer activity, the development of DSFbased cancer therapy has been hampered by its poor solubility in biological fluid and instability in gastric juice and bloodstream [31].…”
Section: Introductionmentioning
confidence: 99%